Craniofacial metastases: a 20-year survey - Thiele, Oliver C.; Freier, Kolja; Bacon, Claire; Flechtenmacher, Christa; Scherfler, Sebastian; Seeberger, Robin (Journal of cranio-maxillofacial surgery, 2011)
In this study we analysed the long-term prognosis of 52 patients with distant metastases to the craniofacial area. All patients were treated in our department between 1989 and 2009. Possible predictive factors for the overall survival prognosis like age, gender, histopathological type of the metastasis, location and tissue structure of the area in the head and neck region, time between primary tumour and metastasis and the therapy were evaluated. 62% of the patients with distant metastases in the craniofacial area were male (32/52), the average age was 63 years. Adenocarcinoma was the most common histological type (20/52) and lung (12/52), malignant melanoma of the skin (9/52) and breast (8/52) the most common primary tumour site. In 35% of all patients, the primary tumour was not known at the time of the diagnosis of the craniofacial metastasis, this number reduced to 17% without the patients with a CUP syndrome. Patients survived an average of 14.4 months after manifestation of the metastases and 43.4 months after the manifestation of the primary tumour.
Gesehen am 02.11.2022
Erstmals online zugänglich am 1. November 2010